2023
DOI: 10.3390/jcm12020426
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women with PCOS: Follow-Up Study of a Randomized Controlled Three-Component Lifestyle Intervention

Abstract: Women with polycystic ovary syndrome (PCOS) and excess weight often present with reproductive derangements. The first-line treatment for this population is a multi-component lifestyle intervention. This follow-up study of a randomized controlled trial based on data from the Dutch Perinatal registry was conducted to study the effect of a one-year three-component (cognitive behavioral therapy, healthy diet, and exercise) lifestyle intervention on pregnancy outcomes in women with PCOS and overweight or obesity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(70 reference statements)
0
2
0
2
Order By: Relevance
“…While acknowledging that a decrease in BMI in obese infertile women during the periconceptional period may potentially reduce the rate of adverse perinatal outcomes, the available evidence may not be sufficient to establish the clear benefits of weight loss. Although lifestyle modifications are recommended, the available evidence supporting their effectiveness is of low quality, highlighting the need for additional research [63] [64] [65].…”
Section: Preventionmentioning
confidence: 99%
“…While acknowledging that a decrease in BMI in obese infertile women during the periconceptional period may potentially reduce the rate of adverse perinatal outcomes, the available evidence may not be sufficient to establish the clear benefits of weight loss. Although lifestyle modifications are recommended, the available evidence supporting their effectiveness is of low quality, highlighting the need for additional research [63] [64] [65].…”
Section: Preventionmentioning
confidence: 99%
“…A síndrome é considerada também a causa mais comum de infertilidade por anovulação, podendo, em alguns países, como nos Estados Unidos, representar a principal causa de infertilidade feminina (Loos, et al 2023). A resistência insulínica associada à obesidade está relacionada com piores resultados no tratamento com indutores da ovulação em mulheres com SOP.…”
Section: Introductionunclassified
“…O atual tratamento de primeira linha para mulheres com SOP é uma intervenção multifatorial no estilo de vida (dieta, exercício, terapias comportamentais) para perder peso e prevenir ganho ponderal excessivo (Loos, et al 2023).…”
Section: Introductionunclassified
“…Recent studies have shown that such pregnant women have a significantly increased risk of miscarriage, gestational diabetes, preeclampsia, and pregnancy-induced high blood pressure. Therefore, it is very important to initiate pre-pregnancy screening and monitoring for overweight and obese women with PCOS [14]. Awareness regarding obstetric challenges should increase, whereas further research should be undertaken to better understand this group of patients.…”
mentioning
confidence: 99%